Prevalence and risk factors for obesity among elderly patients living with HIV/AIDS in a low-resource setting. Issue 15 (16th April 2021) - Dakum, Patrick; Avong, Yohanna Kambai; Okuma, James; Sorungbe, Temilade; Jatau, Bolajoko; Nedmbi, Nicaise; Odutola, Michael Kolawole; Abimiku, Alash'le; Mensah, Charles Olalekan; Kayode, Gbenga Ayodele
Abstract : Abstract: Obesity is associated with detrimental changes in cardiovascular and metabolic parameters, including blood pressure, dyslipidemia, markers of systemic inflammation, and insulin resistance. In the elderly living with the human immunodeficiency virus (EPLHIV), and being treated with antiretroviral medications, the obesity complications escalate and expose the elderly to the risk of noncommunicable diseases. Given that over 3 million EPLHIV in sub-Sahara Africa, we assessed the prevalence of obesity and its associated factors among EPLHIV in a low-resource setting. This was a cross sectional study of EPLHIV aged 50 years and older, being treated with antiretroviral medications from 2004 to 2018. HIV treatment data collected from multiple treatment sites were analyzed. Baseline characteristics of the participants were described, and multivariable relative risk model was applied to assess the associations between obesity (body mass index [BMI] ≥30 kg/m 2 ) and the prespecified potential risk factors. Of the 134, 652 in HIV cohort, 19, 566 (14.5%) were EPLHIV: 12, 967 (66.3%) were normal weight (18.5 ⩽ BMI < 25), 4548 (23.2%) were overweight (25 ⩽ BMI < 30), while 2, 051 (10.5%) were obese (BMI ≥30). The average age the normal weight (57.1; standard deviation 6.6) and the obese (56.5; standard deviation 5.5) was similar. We observed that being an employed (relative risk [RR] 1.71; 95% confidence interval [CI] 1.48–2.00; P < .001), educated (RR 1.93; 95% CI 1.54–2.41; P < .001), and presence of hypertension (RR 1.78; 95% CI 1.44–2.20; P < .001), increased the risk of obesity. Also, being male (RR 0.38; 95% CI 0.33–0.44; P < .001), stages III/IV of the World Health Organization clinical stages of HIV (RR 0.58; 95% CI 0.50–0.68; P < .001), tenofovir-based regimen (RR 0.84; 95% CI 0.73–0.96, P < .001), and low CD4 count (RR 0.56; 95% CI 0.44–0.71; P < .001) were inversely associated with obesity. This study demonstrates that multiple factors are driving obesity prevalence in EPLHIV. The study provides vital information for policy-makers and HIV program implementers in implementing targeted-interventions to address obesity in EPLHIV. Its findings would assist in the implementation of a one-stop-shop model for the management of HIV and other comorbid medical conditions in EPLHIV.